Synthesis of modal control of multidimensional linear systems in agricultural production based on linear matrix inequalities - Lobok, Alexey; Goncharenko, Boris; Vikhrova, Larisa; Sych, Maryna (My University, 2018)
A constructive solution to the problem of synthesis of D-stabilizer (modal) regulators measured by output control object based on the construction of the facility monitors certain order on the basis of the theory of linear matrix inequalities (LMI). The described methods for solving the problem not only of direct modal control, but other tasks modal regulations, which demand precise placing the roots in the left half-plane complex is not applied, and only need their belonging to given areas
Keywords: dynamic system; modal control; regulators; D-stability; Luenberger observers; linear matrix inequalities; linear matrix inequalities; динамічна система; модальне керування; регулятори; D-стійкість; спостерігачі Луенбергера; лінійні матричні нерівності; кронекеровий добуток матриць; кафедра автоматизації та комп'ютерних технологій систем управління ім. проф. А.П. Ладанюка